Intrameningioma metastasis: A case-based literature review. (November 2021) - Papadakis, Benjamin Konstantinos; Vorrias, Eleftherios; Bräutigam, Konstantin; Chochlidakis, Nikolaos; Koutsopoulos, Anastasios; Mavroudis, Dimitrios; Vakis, Antonis; Tsitsipanis, Christos
Highlights: Tumor-to-tumor metastasis is rare. "Tumor-to-tumor metastasis" and "collision tumor" are not synonymous. Lung and breast cancer are frequent sites of origin. Vascularisation, metabolic milieu, and tumor microenvironment predispose for host-recipient-interaction. Abstract: A tumor-to-tumor metastasis inside a meningioma is a rare phenomenon. Malignant neoplasms of the breast and lung are the most common primary tumors. Other sites of origin include prostate, renal and gastric neoplasms. The included case files were retrieved from the medical records of the University Hospital of Crete, Greece. A review of the literature was conducted in March 2020 via PubMed. Relevant search results were few. We report a case of a 66-year-old female, with known Small Cell Lung Cancer, who presented with left-sided hemiparesis. The Magnetic Resonance Imaging scan revealed a right frontal extra-axial mass. The patient underwent a craniotomy and a gross total removal of the tumor. Histological examination of the excised mass revealed metastatic adenocarcinoma deposits inside a meningioma: tumor-to-tumor metastasis. Reviewing the available literature, it has been hypothesized that the following factors play a role in the pathophysiology of this phenomenon: progesterone and estrogen receptors, cell-to-cell adhesion molecules, rich vascularization, favorable metabolic, micro-and immunological environment. Meningiomas seem to be the most common type of intracranial neoplasm to host a metastasis. There is a difference between tumor-to-tumor metastasis and collision tumors. The former implies a recipient role of the host tumor, and the latter refers to a co-localization of two different tumors that grow into one another, both being in the same organ. Tumor-to-tumor brain metastasis is a well-described phenomenon but with unclear pathophysiology. Deeper knowledge could be beneficial for its management.